Combining Nature‐Inspired, Graphene‐Wrapped Flexible Electrodes with Nanocomposite Polymer Electrolyte for Asymmetric Capacitive Energy Storage. Issue 19 (15th June 2016) - Tang, Jiayong; Yuan, Ping; Cai, Chuanlin; Fu, Yanbao; Ma, Xiaohua
Abstract : Two kinds of free‐standing electrodes, reduced graphene oxide (rGO)‐wrapped Fe‐doped MnO2 composite (G‐MFO) and rGO‐wrapped hierarchical porous carbon microspheres composite (G‐HPC) are fabricated using a frozen lake‐inspired, bubble‐assistance method. This configuration fully enables utilization of the synergistic effects from both components, endowing the materials to be excellent electrodes for flexible and lightweight electrochemical capacitors. Moreover, a nonaqueous HPC‐doped gel polymer electrolyte (GPE‐HPC) is employed to broad voltage window and improve heat resistance. A fabricated asymmetric supercapacitor based on G‐MFO cathode and G‐HPC anode with GPE‐HPC electrolyte achieves superior flexibility and reliability, enhanced energy/power density, and outstanding cycling stability. The ability to power light‐emitting diodes also indicates the feasibility for practical use. Therefore, it is believed that this novel design may hold great promise for future flexible electronic devices. Abstract : An efficient approach inspired by bubble‐frozen lake is demonstrated toward graphene‐wrapped nanocomposites. Such structures efficiently prevent the aggregation of the inner particles and improve their electrical conductivity, and a combined composite gel electrolyte facilitates the fast diffusion of lithium and electron, rendering a significant improvement in capacitive energy storage.